TEMBUNG LAN GAMBARE KAMUS VISUAL RAGAM DIKSI BAHASA JAWA TINGKAT NGOKO - Edi Jatmiko (Institut Seni Indonesia Yogyakarta, 2014)
Java language as a mother language, has a complicated character, and terraced difficult even forJavanese society itself. The level of complexity in the Java language system is one of the factors that led to theJava language is considered less desirable and not match the needs of the times by the Java community itself.This difficulty is caused by one of the Java language has a complete vocabulary, diction diverse, in one termin Indonesian, can be assorted due to the mention of the Java language that caused chronology. Javanesesociety has the ability to mark the various forms of work in different terms though just because of smalldifferences. Diction of the diversity of conditions in the Java language ngoko level, ie the level of the languagemost widely used Java community need for adequate instructional media. One of the gaps that can beaddressed in greater depth is how to bring learning the Java language into a form that is easily understoodvisual communication method is to create a visual dictionary of the Java language.